Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Which of the following represents the polar equation r = ( cot ( 2 θ ) ) ( csc ( θ ) ) as a rectangular equation?

Which Of The Following Represents The Polar Equation R Cot 2 Θ Csc Θ As A Rectangular Equation class=

Sagot :

Recall the following rules for identifying the rectangular coordinates (x,y) from the polar coordinates (r,θ):

[tex]\begin{gathered} x=r\cos\theta \\ y=r\sin\theta \end{gathered}[/tex][tex]r=\sqrt{x^2+y^2}[/tex]

First, rewrite cot(2θ)csc(θ) in terms of sines and cosines:

[tex]\begin{gathered} r=(\cot2\theta)(\csc\theta) \\ \\ =\frac{\cos2\theta}{\sin2\theta}\cdot\frac{1}{\sin\theta} \\ \\ =\frac{1-2\sin^2\theta}{2\sin\theta\cos\theta}\cdot\frac{1}{\sin\theta} \\ \\ =\frac{1-2\sin^2\theta}{2\sin^2\theta\cos\theta} \end{gathered}[/tex]

Multiply both numerator and denominator by r^3 and order the factors in such a way that the expressions for x and y are made evident:

[tex]\begin{gathered} r=\frac{1-2\sin^2\theta}{2\sin^2\theta\cos\theta} \\ \\ \Rightarrow r=\frac{r^3(1-2\sin^2\theta)}{r^3(2\sin^2\theta\cos\theta)} \\ \\ =\frac{r(r^2-2(r^2\sin^2\theta))}{2(r^2\sin^2\theta)(r\cos\theta)} \\ \\ =\frac{r(r^2-2(r\sin\theta)^2)}{2(r\sin\theta)^2(r\cos\theta)} \end{gathered}[/tex]

Simplify and replace the expressions for rsin(θ) and rcos(θ) as well as r:

[tex]\begin{gathered} r=\frac{r(r^2-2(r\sin\theta)^2)}{2(r\sin\theta)^2(r\cos\theta)} \\ \\ \Rightarrow1=\frac{(r^2-2(r\sin\theta)^2)}{2(r\sin\theta)^2(r\cos\theta)} \\ \\ \Rightarrow1=\frac{(x^2+y^2-2(y)^2)}{2(y)^2(x)} \\ \\ \Rightarrow1=\frac{(x^2+y^2-2y^2)}{2y^2x} \\ \\ \Rightarrow1=\frac{(x^2-y^2)}{2y^2x} \\ \\ \Rightarrow2y^2x=x^2-y^2 \end{gathered}[/tex]

Isolate y^2 from the equation:

[tex]\begin{gathered} \Rightarrow2y^2x+y^2=x^2 \\ \\ \Rightarrow y^2(2x+1)=x^2 \\ \\ \Rightarrow y^2=\frac{x^2}{2x+1} \end{gathered}[/tex]

Therefore, the polar equation can be written as a rectangular equation as follows:

[tex]y^2=\frac{x^2}{2x+1}[/tex]

We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.